On Cubic Operators Defined on Finite-Dimensional Simplexes - Rozikov, U. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We introduce the concept of cubic operator. For one class of cubic operators defined on finite-dimensional simplexes, a complete description of the behavior of their trajectories is given. The convergence of Cesaro means is established.